Anti-inflammatory activity of craterostigma pumilum (hochst) is associated with hyperalgesia - John, Mwonjoria; Aliyu, Umar; Kevin, Juma; Titus, Kahiga; Piero, Ngugi; David, Mburu; Alphonse, Wanyonyi; Charles, Githinji; Joseph, Ngeranwa (International Journal of Pharmacology and Toxicology, 2016)
Inflammation and pain are ubiquitous signs and symptoms of a large number of ailments affecting humanity. There are equally as many methods and substances that are used as remedies for the conditions. Examples of remedies used include herbal extracts such those of genus Craterostigma among others. In Kenya, some plants from this genus are used as folklore remedy for toothache, joint and muscle pains. Interestingly, in spite of their use, there is no scientific study that has been instituted to evaluate their efficacy. The current study evaluated the anti-inflammatory and antinociceptive effect of both dichloromethane (DCM) and aqueous extract of Craterostigma pumilum using animal models. The anti-inflammatory and antinociceptive effect assays were carried out using formalin induced pedal edema and pain test respectively in white Wister rats. The phytochemical profile of the plant extract was carried out using standard procedures. Both DCM and aqueous extracts exhibited highly significant anti-inflammatory (p < 0.001) effects but no antinociceptive effects. However, the DCM extract showed a very significant (p < 0.001) hyperalgesia. The study renders support to folklore use of the plant for inflammation however it recommends incorporation of an analgesic remedy in the process.